The Effect of a Guided Inquiry Learning Model With A Scientific Approach in Green Chemistry and Global Warming Material On Students Critical Thinking Ability and Learning Motivation - Nur Elisa Hawa T Tarkin; Isana Supiah Yosephine Louise (Postgraduate, University of Mataram, 2023)
This research aims to determine the effects of the guided inquiry learning model implemented with a scientific approach simultaneously on students critical thinking abilities and learning motivation. This research is a quasi-experiment with a pretest-posttest control group design. The research was conducted at SMAN 1, Semarang. The research sample consisted of class X students at SMAN 1, Semarang. The sample consisted of a total of 136 students from class X. The sampling technique used was cluster random sampling. The instruments used in this research consisted of a critical thinking ability test in the form of reasoned multiple-choice questions and a learning motivation questionnaire. The analysis technique used involves the use of multivariate statistics, specifically using the Manova test. The results of the research show that there are significant differences in student’s critical thinking abilities and learning motivation when implementing the guided inquiry learning model with a scientific approach. In general, the combined effect of the guided inquiry learning model with a scientific approach provides an effective contribution of 30.9% of the variance in critical thinking abilities and learning motivation.